Hypoglycemic and Hypocholesterolemic effects of Persea americana Mill. (Avocado) Leaf extract on Diabetic Rattus Norvegicus (Albino rats). - Cajayon, Kathleen Joy S. (2015)
ABSTRACT see Upload (BIO 1422 2015)